Modern methods of development of marine gas hydrate deposits - Bondarenko, V. I.; Kovalevska, I. A.; Prokopenko, K. M. (Technium: Romanian Journal of Applied Sciences and Technology, 2019)
In recent years, there has been a trend around the world towards a constant increase in the consumption of fuel and energy resources, in connection with this there is a significant increase in interest in non-traditional methods of extraction of various energy sources. For many countries, this issue is especially relevant, since the price of natural gas supplied from abroad is growing every year, which negatively affects the economy. Therefore, the need to modernize the structure of the oil and gas complexes and to improve the mechanism for the development of the energy segment, which is possible through the introduction and application of the latest gas hydrate technologies, which will provide an opportunity to obtain additional energy, is obvious.